Why should we care about astrocytes in a motor neuron disease? - Stoklund Dittlau, Katarina; Van Den Bosch, Ludo (Frontiers in Molecular Medicine, 2023)
Amyotrophic lateral sclerosis (ALS) is the most common motor neuron disease in adults, causing progressive degeneration of motor neurons, which results in muscle atrophy, respiratory failure and ultimately death of the patients. The pathogenesis of ALS is complex, and extensive efforts have focused on unravelling the underlying molecular mechanisms with a large emphasis on the dying motor neurons. However, a recent shift in focus towards the supporting glial population has revealed a large contribution and influence in ALS, which stresses the need to explore this area in more detail. Especially studies into astrocytes, the residential homeostatic supporter cells of neurons, have revealed a remarkable astrocytic dysfunction in ALS, and therefore could present a target for new and promising therapeutic entry points. In this review, we provide an overview of general astrocyte function and summarize the current literature on the role of astrocytes in ALS by categorizing the potentially underlying molecular mechanisms. We discuss the current efforts in astrocyte-targeted therapy, and highlight the potential and shortcomings of available models.